Botulinum Toxin A and B for Palmoplantar Hyperhidrosis - Trond Eilertsen; Bjørn Øivind Kvammen; Øystein Grimstad (Adis, Springer Healthcare, 2024)
Abstract Introduction Hyperhidrosis is characterized by unpredictable, uncontrollable and excessive sweating. It occurs at rest and is not related to temperature. Hyperhidrosis is a common disorder that has a negative impact on quality of life (QoL). The aim of this quality assurance study was to investigate how treatment of palmoplantar hyperhidrosis with botulinum toxin A (BTX-A) and botulinum toxin B (BTX-B) led to improvement of patient reported outcome measures related to QoL. Methods A total of 35 patients with palmar and/or plantar hyperhidrosis who had received BTX-A (Dysport®) and BTX-B (NeuroBloc®) for palmar hyperhidrosis and BTX-B for plantar hyperhidrosis were included in this study. In total, palms were injected with a median dose (low to high) of 400 (100-550) units BTX-A and a median dose (low to high) of 200 (200-500) units. BTX-B was used in the thenar and hypothenar areas to avoid muscle weakness. In the soles a total median dose (low to high) of 600 (475-1000) units BTX-B was injected. Results At follow-up 2 weeks post-treatment, patients' Dermatology Life Quality Index (DLQI) score improved from 13 to 2 (p < 0.001). Conclusion We found that BTX-A and BTX-B treatment for palmar hyperhidrosis and BTX-B treatment for plantar hyperhidrosis led to a substantial improvement of QoL.